2005
DOI: 10.1159/000084657
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of <i>L</i>-Arginine Intake on the Impaired Renal Vascular Responses in the Gentamicin-Treated Rats

Abstract: The purpose of this study was to investigate the effect of gentamicin (100 mg/kg/day, i.p.) treatment on endothelium-dependent and -independent vasodilation in isolated perfused rat kidney, and the effect of amino acid L-arginine (in the drinking water, 2.25 g/l) on renal dysfunction induced by gentamicin. When gentamicin-treated groups were compared with the control group, it was observed that BUN and creatinine levels increased significantly. Also, the relaxant responses induced by acetylcholine, sodium nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Infusion of Arg in experimental animals increased renal plasma flow and glomerular filtration rate. So animals were treated with gentamicin or cisplatin-induced nephropathy together with Arg showed a significant amelioration in renal functions as indicated by blood urea nitrogen and creatinine levels [ 57 , 58 ]. Moreover, this dose of Arg (500 mg/kg) has been clinically applied for several other human diseases [ 59 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of Arg in experimental animals increased renal plasma flow and glomerular filtration rate. So animals were treated with gentamicin or cisplatin-induced nephropathy together with Arg showed a significant amelioration in renal functions as indicated by blood urea nitrogen and creatinine levels [ 57 , 58 ]. Moreover, this dose of Arg (500 mg/kg) has been clinically applied for several other human diseases [ 59 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to the previous reports. [ 21 22 ] However, L-arginine diminished the acute tubular necrosis as well. This effect can be due to the other mechanisms in addition to L-arginine-NO pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have demonstrated the beneficial effects of NO in renal pathology. For example, l ‐arginine ( l ‐Arg), a substrate for NOS, protects against cyclosporin 20 and gentamicin 21 nephrotoxicity. Similarly, SNP suppresses renal oxidative damage caused by potassium bromate 22 .…”
Section: Introductionmentioning
confidence: 99%